Ice Business Feasibility Analysis - Netty Lisdiantini; A Doedyk Setiawan; Yosi Affandi (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research is a feasibility analysis of the tube ice business of Madiun State Polytechnic based on planning. The preparation of the Madiun State Polytechnic ice tube business plan consists of several aspects, namely external and internal aspects. External aspects consist of industrial aspects. While the internal aspects consist of marketing aspects, management aspects, human resources aspects, operational and layout aspects, financial aspects and legal aspects. The object of this study is the tube ice business of the Madiun State Polytechnic located in Madiun. Researchers want to develop a business plan related to the ice tube business of Madiun State Polytechnic. The purpose of preparing a tube ice business plan for the Madiun State Polytechnic is to find out if the tube ice business for the Madiun State Polytechnic is feasible or not. Based on the explanation above, it can be concluded that the marketing aspect of Es Poll has a focus on the target market for culinary entrepreneurs and individual consumers. And this ice poll business deserves to be run into a business